Gender Pay Gaps among Highly Educated Professionals: Compensation Components Do Matter - Christian Grund (Institute for the Study of Labor (IZA), 2014)
Making use of panel data from a survey of highly educated professionals, gender pay gaps are explored with regard to total compensation as well as to individual compensation components. The results indicate meaningful male-female wage differentials for this quite homogeneous group of people working in one specific industry: in particular for more experienced employees in higher positions of firm hierarchies with children. Gender pay gaps are much more pronounced for bonus payments than they are for fixed salaries.
Keywords: M52; J31; J33; 330; bonus payments; fixed salaries; gender wage gap; management compensation